Cambridge English Advanced Result: workbook Resource Pack with Key - Gude K. Kathy (Oxford, Oxford University Press, 2018)
This popular and successful course has been revised an updated to reflect the requirements of the 2015 Cambridge English: Advanced (CAE) exam.